Effects of argon/nitrogen sputtering gas on the microstructural, crystallographic and piezoelectric properties of AlN thin films - Abd Samad, Muhammad Izzuddin; Mohd Noor, Mimiwaty; Nayan, Nafarizal; Abu Bakar, Ahmad Shuhaimi; Mansor, Marwan; Mahmood Zuhdi, Ahmad Wafi; Hamzah, Azrul Azlan; Latif, Rhonira (Elsevier, 2023)
The growth of highly crystalline c-plane AlN 〈002〉 is extremely difficult, entailing high temperature and ultrahigh vacuum condition. In sputtering technique, the addition of nitrogen into argon sputtering gas can significantly assist the formation of AlN 〈002〉 at low temperature. We incorporated purified nitrogen gas and observed the consistent formation of single crystal 〈002〉 AlN thin film layer sputter-deposited on Mo/Si substrate from the AlN ceramic target. Small presence of oxygen content within AlN crystal relates to the preferential growth of AlN 〈002〉. High oxygen content in AlN thin film due to the use of unpurified nitrogen and argon only sputtering gas prefers the formation of AlN 〈100〉. Different AlN crystal structure has shown distinct thin film properties and piezoelectric response. This work provides a method to control the crystal structure of the sputter-deposited AlN thin film layer, either c-plane AlN 〈002〉, a-plane AlN 〈100〉 or polycrystalline AlN.